Improving PM-NOx trade-off with paraffinic fuels: A study towards diesel engine optimization with HVO. (1st April 2020) - Dimitriadis, Athanasios; Seljak, Tine; Vihar, Rok; Žvar Baškovič, Urban; Dimaratos, Athanasios; Bezergianni, Stella; Samaras, Zissis; Katrašnik, Tomaž
Highlights: At default settings HVO produce lower PM and HC emissions compared to petrodiesel. At default engine settings NOx emissions are similar for HVO and petrodiesel. MIT retardation with HVO results in lower PM and NOx compared to petrodiesel. Retardation of MIT is the optimum strategy for HVO fuel. Abstract: The current work investigates the impact of a paraffinic fuel on combustion and emissions of a diesel engine, examining alternative injection strategies for the full exploitation of the fuel characteristics. The paraffinic fuel used was the HVO (Hydrotreated Vegetable Oil) produced by Neste Oil with the brand name NEXBTL. The study was conducted on a light-duty turbocharged and aftercooled common-rail diesel engine, with both HVO and a conventional diesel fuel. Four steady-state operating points were examined, at low and medium engine speeds (1500 and 3000 rpm) and loads (35 and 100 Nm), typical of daily driving of a passenger car. The key contribution of the study is a comprehensive analysis of the phenomena influencing the crank angle resolved in-cylinder parameters, as well as interlinking the effects of different variations of injection pressure (default and 300 bar higher), pilot injection timing (default and ± 5°CA) and main injection timing (default and ± 2°CA) on gaseous emissions and particulate matter (PM). The findings have shown that at default engine settings the use of HVO results in up to 40% reduction of engine-out PM and HC emissions without appreciable changes in NOx emissions. The significant reduction of engine-out PM levels, facilitates the adoption of measures for NOx emissions limitation. The latter are reduced by up to 20% when the main injection timing is retarded (by 2° CA in the present study), while PM emissions are still kept well below the respective diesel fuel levels.